sn-1,2-Diacylglycerols and phorbol diesters stimulate thromboxane synthesis by de novo synthesis of prostaglandin H synthase in human promyelocytic leukemia cells. - Goerig, M (1987)
We studied the regulation of thromboxane (TX) synthesis in promyelocytic leukemia cells during macrophage differentiation. Cells treated with 12-O-tetradecanoylphorbol-13-acetate (TPA) showed rates of TXB2 synthesis from exogenous arachidonic acid that exceeded that of control cells by a factor of up to 81. Cells treated with sn-1,2-dioctanoylglycerol (diC8) showed similarly high TXB2 synthesis rates when diC8 was added concomitantly with a subthreshold concentration of TPA or when given in multiple doses. These activities depended on de novo synthesis of prostaglandin H (PGH) synthase because: microsomal PGH synthase activity showed large increases in Vmax values, and mass measurements of PGH synthase revealed the presence of PGH synthase in differentiating cells whereas the enzyme was undetectable in control cells. These results indicate that macrophage differentiation is associated with stimulation of TXB2 synthesis that requires both activation of protein kinase C and de novo synthesis of PGH synthase.